Studi Identifikasi Daerah Sebaran Banjir di DAS Peusangan dengan Pemodelan HEC-RAS 2D Unsteady Flow - Ghina Rahmatika Asril; Cut Dwi Refika; Maimun Rizalihadi; Nina Shaskia (Institut Teknologi Bandung, 2025)
Abstract The Peusangan Watershed is a watershed located in Aceh Province. According to data from the Aceh Irrigation Agency, the downstream area of ​​the Peusangan Watershed frequently experiences flooding, resulting in environmental damage and significant economic losses. Flood management efforts that have been undertaken include the construction of retaining walls. Furthermore, studies are needed to assess the inundation conditions, including flood inundation modeling using HEC-RAS 2D unsteady flow software and ArcGIS 10.5 for mapping the affected areas. The modeling results indicate that the flood inundation areas for return periods of 2, 5, 10, 25, 50, and 100 years are, respectively, 37,38 km², 78,13 km², 95,17 km², 112,82 km², 120,67 km², and 126,28 km². The model validation of flood distribution points for each return period was 28,57%, 66,67%, 71,43%, 76,19%, 90,48%, and 90,48%, respectively. The mapping results based on the classification of downstream sub-districts with return periods of 2, 5, 10, and 25 years inundated two sub-districts, namely Peusangan Selatan Sub-district and Peusangan Siblah Krueng Sub-district, while the return periods of 50 and 100 years inundated three sub-districts, including Peusangan Sub-district. Keywords : Flood, Peusangan Watershed, arcgis, HEC-RAS 2D.